1992
DOI: 10.1136/hrt.67.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and silent myocardial ischaemia in hypertensive patients with left ventricular hypertrophy.

Abstract: Objective-To assess the prevalence of symptomatic and silent myocardial ischaemia in patients with hypertensive left ventricular hypertrophy.Design-Cross sectional study. Setting-University department of medical cardiology.Patients-90 patients (68 men and 22 women; mean age 57 (range 25 to 79)) with left ventricular hypertrophy due to essential hypertension.Interventions-48 hour ambulatory ST segment monitoring (all patients), exercise electrocardiography (n = 79), stress thallium scintigraphy (n = 80), corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In fact, perfusion imaging is more reliable than radionuclide angiography in identifying coexistent CAD in hyperten sive patients with LVH [45]. Using thallium imaging it has been shown that HYP patients with LVH have a high prevalence of both silent and symptomatic CAD [46]. For this aim, two groups of patients have been compared tak ing into consideration the age, sex.…”
Section: The Role O F Myocardial L Vhmentioning
confidence: 99%
“…In fact, perfusion imaging is more reliable than radionuclide angiography in identifying coexistent CAD in hyperten sive patients with LVH [45]. Using thallium imaging it has been shown that HYP patients with LVH have a high prevalence of both silent and symptomatic CAD [46]. For this aim, two groups of patients have been compared tak ing into consideration the age, sex.…”
Section: The Role O F Myocardial L Vhmentioning
confidence: 99%
“…The increased total peripheral resistance in hypertension is shared by all organ circulations including the coronary one. Consequently, Marcus and associates (8) introduced the concept of coronary flow reserve which has been extremely useful to explain coronary insufficiency and silent ischemia associated with hypertensive heart disease (HHD) and other cardiovascular diseases (8)(9)(10)29). Using this innovation, coronary blood flow is measured before and after physiological (e.g., exercise, ventricular pacing) or pharmacological (e.g., carbochrome, papaverine, dipyridamole, adenosine) interventions, and the difference between the two coronary blood flow and vascular resistance measurements provides an excellent index of coronary flow reserve and minimal coronary vascular resistance.…”
Section: Coronary Insufficiency Coronary Flow and Flow Reservementioning
confidence: 99%
“…Myocardial ischemia is one of the important causes of arrhythmia and MTWA positivity [17]. Changes associated with hypertension in myocardium, arterial walls, coronary artery diameter, and blood viscosity may lead to myocardial ischemia by causing supply-demand mismatches in coronary blood flow [18][19][20][21]. Other than fibrosis and ischemia, adrenergic neural activation also plays a significant role in life-threatening cardiac arrhythmias and sudden death in hypertensive patients [22].…”
Section: Discussionmentioning
confidence: 99%